On the Dispersion of Gases Discharged to the Chimney of a Thermal Power Plant - Adrian LEOPA (The Annals of “Dunarea de Jos” University of Galati. Fascicle IX, Metallurgy and Materials Science)
This paper presents a theoretical study on the dispersion of gaseous pollutants from a natural gas thermal power plant in the event of a malfunction. Using the Gaussian model, the dispersion of nitrogen oxides generated by such a thermal power plant was evaluated across different atmospheric stability classes. This allowed for an assessment of whether the concentration of this pollutant meets the maximum permissible limits established by Romanian laws, as well as an identification of the affected areas.